ANALISIS HUKUM HAK – HAK ATAS ANAK AKIBAT DISPENSASI NIKAH DI PENGADILAN SUNGGUMINASA: LEGAL ANALYSIS OF CHILDREN'S RIGHTS DUE TO MARRIAGE DISPENSATION AT SUNGGUMINASA COURT - Akbar, M.; Tira, Andi; M. Jafar, Juliati (Faculty Of Law Bosowa University, 2022)
This study aims to determine: 1). How is the implementation of legal protection against the granting of a marriage dispensation application at the Sungguminasa Religious Court 2). How are the rights of children as a result of the marriage dispensation at the Sungguminasa Religious Court. The research method used is field research with data collection techniques, namely interviews and documentation and analyzed qualitatively. The results showed 1). The implementation of legal protection for the granting of a marriage dispensation application at the Sungguminasa religious court. Regarding the Marriage Dispensation at the Sungguminasa Religious Court, the judge basically understood well, in which case the judge in deciding the decision on a marriage dispensation case referred to the Compilation of Islamic Law (KHI) and Law Number 35 of 2014 concerning Child Protection. In determining the application for a marriage dispensation, the judge has used various considerations and legal grounds related to the granting of a marriage dispensation. Although the age limit for marriage requirements has been regulated, at the practical level the application is flexible. This means, if it is a case of an emergency in order to avoid mafsadah (damage) then dispensation must be given and immediately married. 2). As a result of the stipulation of marriage dispensation at the Sungguminasa Religious Court, it causes the rights of the child to be unfulfilled. In this case, the child loses the opportunity to continue his education, loses the opportunity to develop and express, be creative, and take advantage of free time. If viewed from the application of Law Number 35 of 2014 concerning Child Protection against marriage dispensation cases at the Sunggumiansa Religious Court, it has not been effective because in this case the form of protection provided by the Religious Courts to applicants for marriage dispensation is limited to protecting children from discriminatory treatment regardless of the rights of the child being protected. other.